2020
DOI: 10.1186/s43045-020-00067-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related anxiety disorder in Iraq during the pandemic: an online cross-sectional study

Abstract: Background The COVID-19 outbreak is an unprecedented global public health burden, which popped up in China in late 2019 to early 2020 and distributed worldwide rapidly. Indeed, this pandemic transmission has raised global physical and mental health concerns. Mental health issues that concur with this public health emergency may pose anxiety, depression, and posttraumatic stress disorder. In Iraq, there are no registered known data on the psychological consequence of the public during the communicable disease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(31 reference statements)
3
21
1
Order By: Relevance
“…Women experience more health anxiety than males as a result of a public health issue and they experience more fear, and this can be observed due to gender differences [ 21 , 22 ]. Furthermore, women were the most affected in a study conducted in Peru among 3887 persons on the fear perception of the COVID-19 vaccination [ 2 ], as it was in Iraq [ 23 ], which is consistent with the ongoing study. Another notable finding in this study is that young people and mature adults were more fearful of the COVID-19 vaccines, which is consistent with other studies conducted during the COVID-19 pandemic in the Kurdistan area [ 24 ], Iraq [ 23 ], Austria [ 25 ], and the UK [ 26 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Women experience more health anxiety than males as a result of a public health issue and they experience more fear, and this can be observed due to gender differences [ 21 , 22 ]. Furthermore, women were the most affected in a study conducted in Peru among 3887 persons on the fear perception of the COVID-19 vaccination [ 2 ], as it was in Iraq [ 23 ], which is consistent with the ongoing study. Another notable finding in this study is that young people and mature adults were more fearful of the COVID-19 vaccines, which is consistent with other studies conducted during the COVID-19 pandemic in the Kurdistan area [ 24 ], Iraq [ 23 ], Austria [ 25 ], and the UK [ 26 ].…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, women were the most affected in a study conducted in Peru among 3887 persons on the fear perception of the COVID-19 vaccination [ 2 ], as it was in Iraq [ 23 ], which is consistent with the ongoing study. Another notable finding in this study is that young people and mature adults were more fearful of the COVID-19 vaccines, which is consistent with other studies conducted during the COVID-19 pandemic in the Kurdistan area [ 24 ], Iraq [ 23 ], Austria [ 25 ], and the UK [ 26 ]. These age groups are using technology more than the elderly.…”
Section: Discussionsupporting
confidence: 76%
“…Getting weight and/or perception of gaining weight can impart negative impact on body and psychological and well-being of individuals on immune system. Recent studies have confirmed viral infections of COVID-19 can be more severe among obese (Rychter et al, 2020) and stress and anxiety (Karim et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Getting weight and/or perception of gaining weight can impart negative impact on body and psychological and well‐being of individuals on immune system. Recent studies have confirmed viral infections of COVID‐19 can be more severe among obese (Rychter et al, 2020) and stress and anxiety (Karim et al., 2020). Therefore, it is worth suggesting that besides staying healthy, psychological aspect is also important and helpful in better managing this pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…Almost half (n = 70) of the studies were conducted in China [ 8 , 11 , 23 90 ], followed by 15 studies in India [ 10 , 91 – 104 ], 11 studies in Turkey [ 105 115 ], 10 studies in Saudi Arabia [ 116 125 ], 6 studies in Pakistan [ 126 131 ], 4 studies in Indonesia [ 132 – 135 ] and Nepal [ 136 139 ] respectively, 3 studies in Malaysia [ 140 142 ], Singapore [ 143 145 ], Japan [ 146 148 ] and Iran [ 149 151 ] respectively with 2 studies in Oman [ 152 , 153 ], Jordan [ 154 , 155 ], Philippines [ 156 , 157 ] and Bangladesh [ 158 , 159 ] respectively. Besides, Korea [ 160 ], Qatar [ 161 ], and Iraq [ 162 ] which each had one study, there were also some multinational studies that were conducted, with 2 of them involving several countries in Asian Pacific [ 9 , 163 ] and another one involving both Egypt and Saudi Arabia [ 164 ] (Table A4 in S4 Table ).…”
Section: Resultsmentioning
confidence: 99%